Decentralised content moderation - Paul Friedl; Julian Morgan (Internet Policy Review, 2024)
Decentralised content moderation describes and potentially advocates for moderation infrastructures in which both the authority and the responsibility to moderate are distributed over a plurality of actors or institutions.
Keywords: 300; Content moderation; Platform governance; Protocol-based infrastructure; Fediverse